2018
DOI: 10.1021/acs.jpcc.8b10288
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic RNA Oligomerization at the Mineral–Water Interface: An Insight into the Adsorption–Polymerization Relationship

Abstract: Nonenzymatic RNA polymerization, a major challenge in understanding the origins of life on early Earth, was previously achieved in the presence of montmorillonite clay and high magnesium concentrations (∼75 mM), but the molecular interactions promoting ribonucleotide oligomerization remain unknown. High adsorption capacity of minerals is generally assumed to favor polymerization efficiency; however, this relationship was never shown. Here we examined the relationship between ribonucleotide adsorption affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
(170 reference statements)
1
15
0
Order By: Relevance
“…As described earlier, biological polymers such as oligonucleotides and oligopeptides are products of condensation reactions and can be synthesized when their solutions are exposed to multiple wet-dry cycles in acidic fresh water (Rajamani et al, 2008;Toppozini et al, 2013;da Silva et al, 2014;DeGuzman et al, 2014;Forsythe et al, 2015;Rodriguez-Garcia et al, 2015;Himbert et al, 2016;Misuraca et al, 2017;Yu et al, 2017). Mineral surfaces and peptides may play roles such as nonenzymatic polymerization in early steps in life's origins and bear further investigation (Dalai and Sahai, 2018;Kaddour et al, 2018). If lipids are present during a wet-dry cycle, polymers are encapsulated to form protocells (Deamer and Barchfeld, 1982;Apel et al, 2002).…”
Section: Comparative Environments For An Origin Of Lifementioning
confidence: 99%
“…As described earlier, biological polymers such as oligonucleotides and oligopeptides are products of condensation reactions and can be synthesized when their solutions are exposed to multiple wet-dry cycles in acidic fresh water (Rajamani et al, 2008;Toppozini et al, 2013;da Silva et al, 2014;DeGuzman et al, 2014;Forsythe et al, 2015;Rodriguez-Garcia et al, 2015;Himbert et al, 2016;Misuraca et al, 2017;Yu et al, 2017). Mineral surfaces and peptides may play roles such as nonenzymatic polymerization in early steps in life's origins and bear further investigation (Dalai and Sahai, 2018;Kaddour et al, 2018). If lipids are present during a wet-dry cycle, polymers are encapsulated to form protocells (Deamer and Barchfeld, 1982;Apel et al, 2002).…”
Section: Comparative Environments For An Origin Of Lifementioning
confidence: 99%
“…The condensation reactions needed for the formation of RNA phosphodiester bonds are not thermodynamically favorable in aqueous solutions. To circumvent this, microenvironments, such as mineral surfaces, [8] lipid surfaces [9] or water‐ice eutectic phases [10] have been used to facilitate condensation reactions [11,12] . RNA polymerization by nonenzymatic template‐directed primer extension has been achieved but requires high (∼80 mM) concentrations of Mg 2+ and the question remains as to where the primer or template came from.…”
Section: Introductionmentioning
confidence: 99%
“…Montmorillonite clay facilitates the non-enzymatic polymerization of activated mononucleotides. [8,[12][13][14][15][16][17] Effects of various salt-exchanged clays, background electrolyte ions, pH values, minerals, nucleotides and activating groups were examined on the efficiency, [15,[18][19][20][21][22] regioselectivity [15,[23][24][25] and chiral selectivity [26] of the polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although, initial work did not provide high yields for these reactions [11], later work from Ferris and colleagues demonstrated that minerals such as montmorillonite could provide a suitable surface upon which nucleotides could adsorb, favoring their efficient oligomerization [12]. This is a line that researchers are continuing to pursue even to date [13]. Some researchers have also studied the protective effect of minerals that protect RNA from degradation [14].…”
Section: Polymerization Of Nucleotides In the Absence Of Lipidsmentioning
confidence: 99%
“…The effect of minerals can also go beyond mere protection of the RNA molecules from degradation by hydrolysis. In fact, Kaddour et al [13] tested the hypothesis of whether better adsorption of monomers on mineral surfaces would indeed favor increased polymerization. They showed that although adsorption of activated mononucleotide, 2-methylimadzolide of adenosine monophosphate (2-MeImPA), is approximately 10 times higher on zincite (ZnO) than on montmorillonite clay, only montmorillonite acts as a catalyst for 2-MeImPA polymerization.…”
Section: Polymerization Of Nucleotides In the Absence Of Lipidsmentioning
confidence: 99%